2011
DOI: 10.1021/cs2001048
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Catalytic Conversion of Dry Syngas to Ethanol and Higher Alcohols on Cu-Based Catalysts

Abstract: Ethanol and higher alcohols have been identified as potential fuel additives or hydrogen carriers for use in fuel cells. One method of ethanol production is catalytic conversion of syngas (a mixture of CO, H2, CO2, and H2O), derived from biomass, coal, or natural gas. Thermodynamics of CO hydrogenation shows that ethanol is favored as the sole product at conditions of practical interest, but if methane is allowed as product in this analysis, essentially no ethanol is formed at equilibrium. The kinetics of etha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
203
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(219 citation statements)
references
References 121 publications
6
203
0
2
Order By: Relevance
“…Since hydrogenation of CO to hydrocarbon is thermodynamically more favorable than hydrogenation to alcohols, it is understandable that alcohol formation requires selective catalysts [11][12][13][14]. Therefore, a combination of the methanol synthesis catalysts (containing Cu) and the usual F-T catalysts containing transition metal oxides such as Co, Cr can theoretically work to produce high-molecularweight alcohols by CO hydrogenation [15].…”
Section: Introductionmentioning
confidence: 99%
“…Since hydrogenation of CO to hydrocarbon is thermodynamically more favorable than hydrogenation to alcohols, it is understandable that alcohol formation requires selective catalysts [11][12][13][14]. Therefore, a combination of the methanol synthesis catalysts (containing Cu) and the usual F-T catalysts containing transition metal oxides such as Co, Cr can theoretically work to produce high-molecularweight alcohols by CO hydrogenation [15].…”
Section: Introductionmentioning
confidence: 99%
“…Higher alcohols are synthesized due to the alkali residues such as K + and Na + remaining in the catalysts from their manufacturing [31], which affects production of formyl species as the key precursor. These alkali cations and their OH -anions serve as the active centers to adsorb and activate CO and methanol and produce formate [32]. Hydrogenation of the formate produces surface formyl species, and formaldehyde can be produced either from hydrogenation of the formyl species or dehydrogenation of methanol via surface OH -.…”
Section: Mechanism Of Impurity Formationmentioning
confidence: 99%
“…The higher alcohol amounts can be lowered by decreasing the alkali amount on the catalyst [38,39], increasing the space velocity [34], increasing H 2 /CO ratio [36], and decreasing methanol partial pressure [4]. It has been reported that synthesis of higher alcohols are favored within 553-583 K over Cu-based catalysts with promotors [32]. The amounts of esters and ketones are most probably in equilibrium with the corresponding alcohols by hydrogenation, which is strongly affected by the hydrogen partial pressure [4].…”
Section: Kinetics Of Ethanol Formationmentioning
confidence: 99%
“…Alternatively, syngas can be fed to a catalytic reactor to synthesize ethanol 15) . An ideal catalyst is rhodium-based which shows both high activity and selectivity.…”
Section: ) ~ 13)mentioning
confidence: 99%